(3GdYbO GdaQjOs - (3GHf YHO QHg , CMeO Hf eMeO Hf YHO QHg Hf MHjH Hf MOjQ Hf SGde, CHh YeQ,J (B328 (3g` s
(3ChdgG (B:s
(3gPG GdOjf eJjf aChZd ajg HQab, jG Hfj Ef GdMSfI Hjf GdSjFJjf jYfj Cf GdOjf Hjf GdEaQGW hGdJbUjQ, hChd YfhGf HYO Pdc (B"(3Gdbhd aj GdbOQ(B" s
(3BNQgG (B:s
(3ef (B"(3HGH GdWGYhf(B" (3deG hbY GdWGYhf GdLGQa CWGa GdfGS HGdMSf (B"(3ef CMH GdehJ hef cQgg(B" (3hGdMeO ddg hMOg s
(3GdLRA GdKGdK(B: (3GdjGbhJI hGdLhgQI hGdReQOIs
(3GfXQ GdLRA GdChd Qbe (B890 (3COHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B207 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B115s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B41 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs